“Plants brought back to life”: An exploration of female adolescent survivors’ experiences of sexual abuse, healing and resilience - Jarabe, Maria Lourdes; Rahayuwati, Laili (Jurnal Keperawatan Padjadjaran, 2024)
Background: Sexual abuse is a significant issue for adolescent girls in the Philippines. This study explores the experiences of survivors, focusing on their journeys of healing and resilience. Methods: This Interpretative Phenomenological Analysis study aimed to understand the lived experiences of Filipino adolescent girls who survived sexual abuse through four key questions, namely: 1) How did each participant perceive their experience? 2) What coping mechanisms did they employ to deal with the trauma? 3) How did the abuse impact their self-perception and purpose in life? 4) What symbols or meanings do they associate with their experiences? Results: The analysis identified six superordinate and sixteen subordinate themes. These included: 1) sense of loss – participants described a deep sense of loss due to the abuse; 2) healing as a process – healing was perceived as a gradual and ongoing journey; 3) supportive environment – supportive relationships played a crucial role in coping; 4) growing faith in God – faith emerged as a significant source of strength; 5) reclaiming the sense of self – regaining a sense of self-worth was a central aspect of healing; and 6) altruism – the desire of helping others emerged as a meaningful way to cope. Conclusions: The participants’ experiences can be likened to a resilient plant that, despite facing near-destruction, revives with renewed strength. Family dynamics played a crucial role in the girls’ experiences of abuse. A culture of silence and fear emerged as a significant theme in their narratives. Additionally, the ambiguity and conflicting emotions surrounding accountability for perpetrators within close families posed complex challenges. This research provides valuable insights into the experiences of sexually abused Filipino adolescent girls, informing nursing practice. The findings enable nurses to offer culturally sensitive, trauma-informed care and develop targeted support interventions. Incorporating these insights into nursing education will enhance students’ competencies in trauma response, cultural sensitivity, and therapeutic communication with abuse survivors, leading to improved assessment protocols and care strategies.